(untitled) (Psychology Travelogs, 2025)
The mental health of ukrainians has significantly deteriorated due to the challenges of war, daily stress, uncertainty, and loss of a sense of security. Psychological trauma has become a common occurrence in most families: war, explosions, and deaths of loved ones affect the human psyche. The importance and relevance of the problem lies in the transmission of traumatic experiences between generations, trauma can spread in space and time. The descendants of people who survived the war "inherit" the consequences of unresolved psychological problems of the first generation and pass them on to the next. In these processes, time loses its meaning – they can last for centuries, as the need to deal with this legacy remains in the group unconscious. Without realizing that we are reliving traumatic events that happened many decades ago, we can become heirs to fears as if these feelings belong to us.By identifying the source of our intergenerational trauma, we can leave this traumatic experience in the past. Appropriating new positive and safe experiences, finding inner support, meaning, creating new goals, developing new skills - all this helps in overcoming the trauma. Recovery from trauma can lead to qualitatively new forms of social progress. Sometimes the trauma itself can be a source for rediscovering lost resources. The article analyzes contemporary research on transgenerational transmission of traumatic experiences. It considers the impact of traumatization in the context of resources and mechanisms for healing the psyche. The focus shifts to the strengths of the personality, the psyche’s ability to heal itself and adapt. An important role is given to the search for possible ways to overcome, the epigenetic mechanisms of collective trauma and personal transformations during and after psychological trauma are examined, and the resources that people develop as a result of traumatization are identified.